Influential Factors on Discontinuation of Intrauterine Contraceptive Device - G Ebrahim Taheri; G Khosheh Mehri; M Saffari; S Moslemian (Tehran University of Medical Sciences, 2008)
Background & Aim: Choosing proper method for contraception can help to reduce prevalence of unwanted pregnancy and unsafe abortions. IUD is one of the most trustable effective, and long-term contraceptive methods. The periodical study for recognition of the discontinuation factors is important in family planning and population control. Thus, the study was designed to determine the factors influencing the IUD discontinuation among women referring to Tehran;apos south health care centers. Methods & Materials: In this descriptive study, 400 women attending to the health care centers in south Tehran in order to discontinue their IUDs were selected randomly. Data were gathered using questionnaires and analyzed using statistical tests such as chi-square and T-test. Results: The mean IUD duration usage was 29.5±27.88 months. The main complication was bleeding that was reported by 44% of the clients. Infection 36.5% spotting 20.5% pain 12.3% and explosion 11.3% were the other causes of discontinuation, respectively. There was a significant correlation between the discontinuation and complications (P<0.001), husbands;apos education level (P=0.01), and usage duration (P=0.04). Conclusion: The study showed that the most common reason for IUD removal was its side effects. It seems considering appropriate policies could decrease the complications and increase the usage duration.